The data industry : the business and economics of information and big data - Tang, Chunlei (Online access with DDA: Askews (Economics), 2016)
The Data Industry: The Business and Economics of Information and Big Data is a resource for practitioners in the data science industry, government, and students in economics, business, and statistics.